1996
DOI: 10.1084/jem.183.2.651
|View full text |Cite
|
Sign up to set email alerts
|

Physiological regulation of early and late stages of megakaryocytopoiesis by thrombopoietin.

Abstract: SummaryThrombopoietin (TPO) has recently been cloned and shown to regulate megakaryocyte and platelet production by activating the cytokine receptor c-mpl. To determine whether TPO is the only ligand for c-mpl and the major regulator of megakaryocytopoiesis, TPO deficient mice were generated by gene targeting. TPO -/-mice have a >80% decrease in their platelets and megakaryocytes but have normal levels of all the other hematopoietic cell types. A gene dosage effect observed in heterozygous mice suggests that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
263
2
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(272 citation statements)
references
References 26 publications
6
263
2
1
Order By: Relevance
“…At the mature cell level, mutations in c-Mpl and Kit affect the thrombopoietic and erythropoietic lineages, respectively. 7,15,22,23 Moreover, although most other mature lineages are not affected in either single mutant, they both have deficiencies at the stem cell level. 8,[16][17][18]24 We demonstrate here, in double-mutant c-Mpl Ϫ/Ϫ Kit Wv/Wv mice, which lack both Tpo and SF receptors, that these 2 cytokine pathways contribute overlapping and nonredundant actions in mature and multipotential hematopoietic compartments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the mature cell level, mutations in c-Mpl and Kit affect the thrombopoietic and erythropoietic lineages, respectively. 7,15,22,23 Moreover, although most other mature lineages are not affected in either single mutant, they both have deficiencies at the stem cell level. 8,[16][17][18]24 We demonstrate here, in double-mutant c-Mpl Ϫ/Ϫ Kit Wv/Wv mice, which lack both Tpo and SF receptors, that these 2 cytokine pathways contribute overlapping and nonredundant actions in mature and multipotential hematopoietic compartments.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Tpo or c-Mpl knock-out mice have severe thrombocytopenia, with an 80% reduction in the number of circulating platelets. 7,22,23 c-Mpl Ϫ/Ϫ mice also have decreased numbers of clonogenic progenitor cells in multiple lineages and approximately 7-fold reduced competitive repopulation ability. 8,24 Tpo alone supports HSC survival in vitro 25,26 and acts synergistically with other early-acting factors to induce HSC division.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, homozygous TPO or c-mpl knock-out mice exhibit a profound but not lethal thrombocytopenia. 5,6 In vitro and in vivo experiments have shown that TPO is the most potent growth factor for megakaryocyte (MK) differentiation, acting on different developmental stages including MK progenitors, promegakaryoblasts and MK. 7,8 Daily TPO injection to animals including mice and primates increased platelet count up to 10-fold the control value in a few days.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experiments have shown that while TPO alone does promote the proliferation and maturation of megakaryocytes during early endomitotic stages, the effect on maturation is muted during the later endomitotic stages. 6,7 However, of most interest was the finding that although mice lacking TPO exhibited a drastic decrease in the number of platelets and cells of the megakaryocytic lineage, these mice remained healthy and their platelets functioned normally. 8 This result implies that TPO-independent mechanisms for megakaryopoiesis and platelet production exist.…”
Section: Introductionmentioning
confidence: 99%